What's in Your Wallet? The Tax Treatment of Cryptocurrencies - Katherine Baer; Ruud A. De Mooij; Shafik Hebous; Michael Keen (Center for Economic Studies and ifo Institute (CESifo), 2023)
Policymakers are struggling to accommodate cryptocurrencies within tax systems not designed to handle them; this paper reviews the issues that arise. The greatest challenges are for implementation: crypto's quasi-anonymity is an inherent obstacle to third-party reporting. Design problems arise from crytocurrencies' dual nature as investment assets and means of payment: more straightforward is a compelling case for corrective taxation of carbon-intensive mining. Ownership is highly concentrated at the top, but many crypto investors have only moderate incomes. The capital gains tax revenue at stake worldwide may be in the tens of billions of dollars, but the more profound risks may ultimately be for VAT/sales taxes.
Keywords: E62; H25; H32; 330; cryptocurrency; virtual assets; tax evasion; tax compliance; Bitcoin